Green synthesis of Piper nigrum copper-based nanoparticles: in silico study and ADMET analysis to assess their antioxidant, antibacterial, and cytotoxic effects - Kiranmayee, Modumudi; Rajesh, Nambi; Vidya Vani, M.; Khadri, Habeeb; Mohammed, Arifullah; Chinni, Suresh V.; Ramachawolran, Gobinath; Riazunnisa, Khateef; Moussa, Ashaimaa Y. (Frontiers in Chemistry, 2023)
Nanobiotechnology is a popular branch of science that is gaining a staggering interest among scientists and researchers as it allows for the green manufacturing of nano-particles by employing plants as reducing agents. This method is safe, cheap, reproducible, and eco-friendly.In this study, the therapeutic property of Piper nigrum fruit was mixed with the antibacterial activity of metallic copper to produce copper nanoparticles. The synthesis of copper nanoparticles was indicated by a color change from brown to blue. Physical characterization of PN-CuNPs was done by using UV-vis spectroscopy, FTIR, SEM, EDX, XRD, and Zeta analyzer. PN-CuNPs exhibited potential antioxidant, antibacterial and cytotoxic activities. PN-CuNPs have shown enhanced free radical scavenging activity in a concentration-dependent manner, reaching maximum values of 92 %, 90 % and 86 % with DPPH, H2O2 and PMA tests, respectively. The antibacterial zone of inhibition of PN-CuNPs was the highest against S. aureus (23 mm) and the lowest against E. coli (10 mm). In vitro cytotoxicity of PN-CuNPs was demonstrated against MCF-7 breast cancer cell lines. PN-CuNPs showed 80 % in vitro cytotoxicity against MCF-7 breast cancer cell lines. Furthermore, more than 50 components of Piper nigrum extract were selected and subjected to in-silico molecular docking using the C-Docker protocol in the binding pockets of glutathione reductase, E. coli DNA gyrase topoisomerase II and EGFR tyrosine to discover their druggability. Pipercyclobutanamide A (26), pipernigramide F (32) and pipernigramide G (33) scored the highest Gibbs free energy at 50.489, 51.9306, 58.615 Kcal/mol, respectively. The ADMET/TOPKAT analysis confirmed the favorable pharmacokinetics, pharmacodynamics and toxicity profiles of the three promising compounds. The present in silico analysis helps us to understand the possible mechanisms behind the antioxidant, antibacterial, and cytotoxic activities of CuNPs and recommends them as implicit inhibitors of selected proteins.